Flexibility of neural circuits regulating mating behaviors in mice and flies - Karigo, Tomomi; Deutsch, David (Frontiers in Neural Circuits, 2022)
Mating is essential for the prosperity of animal species. As mating behaviors and following reproduction are high-risk and energy-consuming processes, it is critical for animals to make adaptive mating decisions. This includes not only finding a suitable mate, but also adapting mating decisions to the animal’s needs and environmental conditions. Internal needs include physical factors (e.g., hunger state) and emotional states (e.g., fear), while external conditions include both social cues (e.g., the existence of predators or rivals) and non-social factors (e.g., food availability). With recent advances in behavioral neuroscience, we are now starting to understand the neural basis of mating behaviors, mainly in genetic model organisms such as mice and flies. However, how internal and external factors are integrated into the nervous system to allow adaptive, state-dependent, mating decisions is less well understood. In this article, we review recent knowledge on the neural basis of state-dependent modulation of mating behaviors from studies in flies and mice. By contrasting the knowledge from these two evolutionary distant model organisms, we discuss potential conserved and diverged neural mechanisms for the control of stated-dependent mating behaviors in invertebrate and vertebrate brains.